Two-year Clinical Experience with the CyPass Micro-Stent: Safety and Surgical Outcomes of a Novel Supraciliary Micro-Stent - Höh, H.; Grisanti, S.; Rau, M.; Ianchulev, S. (Klinische Monatsblätter für Augenheilkunde, 2014)
Purpose: The aim of this study was to evaluate through 2 postoperative years the clinical outcomes associated with a novel supraciliary micro-stent for the surgical treatment of open-angle glaucoma (OAG) when implanted in conjunction with cataract surgery.Patients and Method: In a multicenter, prospective, consecutive case series, 136 subjects (136 eyes) with OAG and requiring cataract surgery with 24-month postoperative data were included. A combined phacoemulsification procedure, with intraocular lens insertion and CyPass Micro-Stent implantation into the supraciliary space of the study eye, was performed. At baseline, all subjects were on glaucoma medication with either uncontrolled intraocular pressure (IOP; ≥ 21 mmHg, Cohort 1, n = 51) or controlled IOP (< 21 mmHg, Cohort 2, n = 85). Glaucoma medications were stopped postoperatively, but could be restarted if needed, at the investigatorʼs discretion. Device-related adverse events, postoperative IOP, best corrected distance visual acuity (BCDVA), and number of IOP-lowering medications were recorded.Results: The micro-stent was successfully implanted in all eyes. At 24 months, 82 subjects remained in the study. No sight-threatening adverse events occurred. The most common adverse events were transient hypotony (15.4 %) and micro-stent obstruction (8.8 %), typically due to iris tissue overgrowth. Fifteen subjects (11 %) required secondary incisional glaucoma surgery. For Cohort 1 (n = 23), mean ± SD IOP was 15.8 ± 3.8 mmHg after 24 months (change, − 37 % ± 19 %). Mean IOP decrease from baseline was statistically significant (p < 0.0001) at months 6, 12, and 24. For Cohort 2 (n = 59), mean ± SD IOP at 24 months was 16.1 ± 3.2 mmHg (change, 0 % ± 28 %). Mean decrease from baseline was statistically significant at months 6 (p = 0.0188) and 12 (p = 0.0356). At 24 months, the mean ± SD number of medications was 1.0 ± 1.1 in Cohort 1 and 1.1 ± 1.1 in Cohort 2. Mean decrease from baseline medication use was statistically significant at months 6 (p < 0.001), 12 (p < 0.001), and 24 (p = 0.0265) in Cohort 1, and at months 6, 12, and 24 (all p < 0.0001) in Cohort 2.Conclusions: CyPass Micro-Stent implantation, in combination with cataract surgery, was associated with minimal complications while substantially lowering IOP and/or use of IOP-lowering medications.
Keywords: CyPass micro stent; safety; surgical outcomes; supraciliary surgery; 2-year follow-up